2023
DOI: 10.1039/d2fo03645b
|View full text |Cite
|
Sign up to set email alerts
|

Anti-glycation and anti-inflammatory activities of anthocyanins from purple vegetables

Abstract: Anthocyanins may be an effective way to reduce the potential risk of chronic diseases induced by glycation and inflammatory. In the present study, the anti-glycation and anti-inflammatory activities of anthocyanins...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Purple cabbage anthocyanins (PCA) extract (250 g kg −1 anthocyanins, w/w) was bought from Xi'an Ruilin Biological Technology Co., Ltd (Shanxi, China). With reference to previous studies, 18 the anthocyanins identified by high performance liquid chromatography-mass spectrometry (HPLC-MS) mainly contain cyanidin-3-(p-coumarolyl)-diglucoside-5-glucoside, pelargonidin-3-(malonyl)-glucoside, cyanidin-3-sophoroside-5-glucoside, and delphinidin-3-glucoside. Yuanye Biological Co., Ltd (Shanghai, China) and Sinopharm Chemical Reagent Co., Ltd (Shanghai, China) provided the chemical and biochemical reagents needed for the studies.…”
Section: Methodsmentioning
confidence: 89%
“…Purple cabbage anthocyanins (PCA) extract (250 g kg −1 anthocyanins, w/w) was bought from Xi'an Ruilin Biological Technology Co., Ltd (Shanxi, China). With reference to previous studies, 18 the anthocyanins identified by high performance liquid chromatography-mass spectrometry (HPLC-MS) mainly contain cyanidin-3-(p-coumarolyl)-diglucoside-5-glucoside, pelargonidin-3-(malonyl)-glucoside, cyanidin-3-sophoroside-5-glucoside, and delphinidin-3-glucoside. Yuanye Biological Co., Ltd (Shanghai, China) and Sinopharm Chemical Reagent Co., Ltd (Shanghai, China) provided the chemical and biochemical reagents needed for the studies.…”
Section: Methodsmentioning
confidence: 89%
“…However, peonidin, pelargonidin, and delphinidin glucoside are other major anthocyanins that can be found in these sources . Also, many vegetables and flowers are also rich in anthocyanins, like red cabbage, purplecorn, purple sweet potato, purple cabbage, gynura bicolor and hibiscus calyx. , …”
Section: Basic Information About Anthocyaninsmentioning
confidence: 99%
“…28 Also, many vegetables and flowers are also rich in anthocyanins, like red cabbage, purplecorn, purple sweet potato, purple cabbage, gynura bicolor and hibiscus calyx. 29,30 2.2. Absorption and Transport of Anthocyanin in the Gastrointestinal Tract.…”
Section: Main Classification and Structure Of Dietarymentioning
confidence: 99%
“…Anthocyanins also exert anti-inflammatory effects. Gao et al [ 187 ] showed that anthocyanins from purple vegetables—purple cabbage, purple sweet potato, purple corn and Gynura bicolor —effectively inhibited the production of pro-inflammatory factors such as nitric oxide (NO) and tumour necrosis factor alpha (TNF-α) [ 187 ]. Anthocyanins have also been shown to counteract the progression of obesity and osteoarthritis [ 188 ].…”
Section: The Effects Of Anthocyanins On the Prevention And Supportive...mentioning
confidence: 99%